UPAYA PENCEGAHAN STUNTING MELALUI SOSIALISASI PHBS DI POSYANDU KASIH IBU DESA BULUH MANIS KABUPATEN BENGKALIS - Lumbanraja, Maha Martabar Mangatas; meka, elsa rahmawati (Komunitas Manajemen Kompetitif, 2023)
Nowadays, stunting has been a problem that must be addressed by all stakeholders in society, not only relying on the Regional Government, but it is also hoped that they can involve universities in their role through the Tri Dharma of Higher Education. With diverse scientific disciplines, universities can apply their knowledge to the community, especially those in rural areas who still have minimal access to information, especially those related to children's health. This Community Service Activity was carried out in the 2023 “Kuliah Kerja Nyata” series, which was held in Pematang Obo Village, Bathin Solapan District, Bengkalis Regency, which was carried out for 40 days in collaboration with the Village Government, School and Village Community. By providing information on the Dangers of Stunting, it is hoped that the community will be able to know the symptoms of stunting in their environment, and can carry out preventive activities, so that children under five can have adequate nutrition and in the future will become superior citizens in various fields.